EVALUATION OF SECTORAL ADVANCEMENT OF EU COUNTRIES IN THE FACE OF THE ALTERNATIVE COMPETITIVENESS – SOCIAL COHESION - Cyrek, Magdalena (Ekonomia i Prawo. Economics and Law, 2014)
The study deals with a problem of inner consistency of aims of EU socio-economic policy, that often takes a form of the alternative: competitiveness – social cohesion. Criteria of political choice, which are not always revealed can lead to formulation of different recommendations and implementation of different solutions also concerning a field of sectoral policy. In the background of the decisive problems, in the text were presented some alternative evaluations of sectoral development of EU-28 countries, which were prepared taking the assumptions of two variants of priorities found in the effectiveness aims or the social aims. There were presented two alternative rankings of countries which were worked out basing on Eurostat statistical data describing 2011 year. To reflect a sectoral advancement in a synthetic way in both cases there was used a method of development model basing on the Euclidian distance. In the first variant the choice of variables was dictated by their significant correlation with GDP per capita, in the second one with Gini coefficient. As a result there was verified a thesis about consistency of models of structural changes from the point of view of realizing aims of competitiveness and cohesion. Results of the analyses indicate that better effects for integrated development can be found within the variant where the attention is focused on social aims. Such model of development is successfully realized by Scandinavian countries. An irrefutable role in modernization processes that favour reconciliation of competitiveness and social cohesion is played by knowledge-intensive sectors, especially of service character.